The Fungsi Pendidik Dalam Perkembangan Sosial Emosional Pada Usia Dini - Ardila, Fernanda (Universitas Nusa Cendana, 2022)
The purpose of this study was to determine the role of the teacher in developing the social emotions of early childhood. The type of research used in this study is a literature study. Literature study is a method used to collect data or sources related to the topic raised in a study. The results of this study indicate that ideally an early childhood child has a sense of empathy for his friends, likes to share, help and cooperate. But seen in the current phenomenon, there are still many young children who are not sensitive to their environment, do not like to work together with friends. If this is allowed and there is no initiative from educators or parents to develop children's social and emotional development, then children can become anti-social and their emotional social development needs to be handled by theschool and parents of early childhood.